Synthesis and in vitro antikinetoplastid activity of polyamine-hydroxybenzotriazole conjugates - Jagu, Elodie; Krauth-Siegel, Renate (Bioorganic & medicinal chemistry, 2017)
Thirteen new polyamine derivatives coupled to hydroxybenzotriazole have been synthesized and evaluated for their in vitro antikinetoplastid activity. Trypanosoma Trypanothione reductase (TryR) was envisioned as a potential target. Among all tested molecules, only one compound, a N3-spermidine-benzotriazole derivative, displayed relevant inhibitory activity on this enzyme but was not active on parasites. The corresponding Boc-protected spermidine-benzotriazole was however trypanocidal against Trypanosoma brucei gambiense with an IC50 value of 1μM and was completely devoid of cytotoxicity. On the intramacrophage amastigotes of Leishmania donovani, a N2-spermidine conjugate of this series, exhibited an interesting IC50 value of 3μM associated with both low cytotoxicity against axenic Leishmania donovani. These new compounds are promising leads for the development of antikinetoplastid agents and their targets have to be deciphered.
Available online 12 October 2016
Gesehen am 27.06.2018